Incidence of and Factors Associated With Prolonged and Persistent Postoperative Opioid Use in Children 0–18 Years of Age. (October 2020) - Ward, Andrew; De Souza, Elizabeth; Miller, Daniel; Wang, Ellen; Sun, Eric C.; Bambos, Nicholas; Anderson, T. Anthony
Abstract : BACKGROUND: Long-term opioid use has negative health care consequences. Opioid-naïve adults are at risk for prolonged and persistent opioid use after surgery. While these outcomes have been examined in some adolescent and teenage populations, little is known about the risk of prolonged and persistent postoperative opioid use after common surgeries compared to children who do not undergo surgery and factors associated with these issues among pediatric surgical patients of all ages. METHODS: Using a national administrative claims database, we identified 175, 878 surgical visits by opioid-naïve children aged ⩽18 years who underwent ≥1 of the 20 most common surgeries from each of 4 age groups between December 31, 2002, and December 30, 2017, and who filled a perioperative opioid prescription 30 days before to 14 days after surgery. Prolonged opioid use after surgery (filling ≥1 opioid prescription 90–180 days after surgery) was compared to a reference sample of 1, 354, 909 nonsurgical patients randomly assigned a false "surgery" date. Multivariable logistic regression models were used to estimate the association of surgical procedures and 22 other variables of interest with prolonged opioid use and persistent postoperative opioid use (filling ≥60 days' supply of opioids 90–365 days after surgery) for each age group. RESULTS: Prolonged opioid use after surgery occurred in 0.77%, 0.76%, 1.00%, and 3.80% of surgical patients ages 0–<2, 2–<6, 6–<12, and 12–18, respectively. It was significantly more common in surgical patients than in nonsurgical patients (ages 0–<2: odds ratio [OR] = 4.6 [95% confidence interval (CI), 3.7–5.6]; ages 2–<6: OR = 2.5 [95% CI, 2.1–2.8]; ages 6–<12: OR = 2.1 [95% CI, 1.9–2.4]; and ages 12–18: OR = 1.8 [95% CI, 1.7–1.9]). In the multivariable models for ages 0–<12 years, few surgical procedures and none of the other variables of interest were associated with prolonged opioid use. In the models for ages 12–18 years, 10 surgical procedures and 5 other variables of interest were associated with prolonged opioid use. Persistent postoperative opioid use occurred in <0.1% of patients in all age groups. CONCLUSIONS: Some patient characteristics and surgeries are positively and negatively associated with prolonged opioid use in opioid-naïve children of all ages, but persistent opioid use is rare. Specific pediatric subpopulations (eg, older patients with a history of mood/personality disorder or chronic pain) may be at markedly higher risk.